A conservative approach to rehabilitate a molar-incisor hypomineralization case - Rodrigo TEMUDO; Patricia NEVES; Irene VENTURA; Luísa LOPES (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Molar incisor hypomineralization is an increasingly common condition in our population. This condition can have great impact on the esthetics, function, and well-being of the child. This paper reports a case of a young patient diagnosed with this condition affecting all the first permanent molars and lower incisors, particularly teeth 31 and 41. The molars were treated with direct resin restorations with cusp coating and the incisors aesthetic was restored with different techniques such as bleaching with sodium hypochlorite, micro-abrasion and resin restorations. This treatment plan aimed to restore the proper teeth function, treat the already existing hypersensitivity and algic complains and to improve the aesthetic of the anterior sector. The presented case shows a conservative approach to deal with the molar incisor hypomineralization condition with satisfactory results after 1-year follow-up.